Digital Storytelling in Indonesian EFL Higher Education: A Mixed-Methods Study of Narrative Writing Development - Yuti Yuniarti (Merwinspy Publisher, 2026)
This study examines the impact of digital storytelling (DST) on the narrative writing skills of English as a Foreign Language (EFL) learners in an Indonesian higher education context. Using a mixed-methods explanatory sequential design, the study included a quasi-experimental phase with pre-tests and post-tests, comparing an experimental group (n=35) with a control group (n=34). The experimental group demonstrated a significant improvement in narrative writing scores, with a large effect size (Cohen’s d = 1.92), particularly in organization, content, and vocabulary. Qualitative data from semi-structured interviews and student reflections revealed that the improvement was driven by increased student motivation, greater ownership of the writing process, and metacognitive gains in narrative structure. Challenges included technical skills and language use, but the findings suggest that DST, supported by sociocultural and multimodal learning theories, is an effective strategy for enhancing EFL narrative writing instruction. These results have practical implications for educators looking to engage students in more authentic and motivating writing tasks.